2021
DOI: 10.1007/s00429-021-02229-4
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal changes in perineuronal nets and parvalbumin neurons in the rat medial prefrontal cortex

Abstract: Perineuronal nets (PNNs) surrounding fast-spiking, parvalbumin (PV) inhibitory interneurons are vital for providing excitatory:inhibitory balance within cortical circuits, and this balance is impaired in disorders such as schizophrenia, autism spectrum disorder, and substance use disorders. These disorders are also associated with altered diurnal rhythms, yet few studies have examined the diurnal rhythms of PNNs or PV cells. We measured the intensity and number of PV cells and PNNs labeled with Wisteria florib… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 128 publications
(157 reference statements)
1
30
1
Order By: Relevance
“…Several studies have shown that environmental enrichment either during early life (Carstens et al, 2016 ; Stamenkovic et al, 2017 ; O’Connor et al, 2019 ) or adulthood (Foscarin et al, 2011 ; Slaker et al, 2016 ) alters PNNs, as does a high-fat diet during adolescence (Reichelt et al, 2019 , 2021 ) and adulthood (Dingess et al, 2018 , 2020 ). Two studies have shown circadian/diurnal changes, with higher numbers or intensity of PNNs in the dark phase in rodents (Pantazopoulos et al, 2020 ; Harkness et al, 2021 ). Given that PNNs are altered in many ways throughout central nervous system development, and their maturation is brain region-specific and generally coincides with the end of critical periods of plasticity (for a recent review see Carulli and Verhaagen, 2021 ), it is not surprising that numerous studies have also demonstrated changes in PNNs or their composition during aging (Tanaka and Mizoguchi, 2009 ; Karetko-Sysa et al, 2014 ; Brewton et al, 2016 ; Foscarin et al, 2017 ; Richard et al, 2018 ; Ueno et al, 2019 ; Mafi et al, 2020 ).…”
Section: Impact Of Physiological Stimuli On Pnnsmentioning
confidence: 99%
“…Several studies have shown that environmental enrichment either during early life (Carstens et al, 2016 ; Stamenkovic et al, 2017 ; O’Connor et al, 2019 ) or adulthood (Foscarin et al, 2011 ; Slaker et al, 2016 ) alters PNNs, as does a high-fat diet during adolescence (Reichelt et al, 2019 , 2021 ) and adulthood (Dingess et al, 2018 , 2020 ). Two studies have shown circadian/diurnal changes, with higher numbers or intensity of PNNs in the dark phase in rodents (Pantazopoulos et al, 2020 ; Harkness et al, 2021 ). Given that PNNs are altered in many ways throughout central nervous system development, and their maturation is brain region-specific and generally coincides with the end of critical periods of plasticity (for a recent review see Carulli and Verhaagen, 2021 ), it is not surprising that numerous studies have also demonstrated changes in PNNs or their composition during aging (Tanaka and Mizoguchi, 2009 ; Karetko-Sysa et al, 2014 ; Brewton et al, 2016 ; Foscarin et al, 2017 ; Richard et al, 2018 ; Ueno et al, 2019 ; Mafi et al, 2020 ).…”
Section: Impact Of Physiological Stimuli On Pnnsmentioning
confidence: 99%
“…Notably, elimination of microglia not only increases PNN coverage, but also improves mouse performance in spatial memory tasks 20 highlighting a potential role for microglia-mediated PNN maintenance in memory consolidation as subsequent studies identified the importance of microglia in “forgetting” and long-term memory 21 , 22 . It has been reported that PNNs are regulated in a circadian and diurnal manner with dramatic remodeling occurring during sleep in both mice and rats 23 , 24 . A daytime decrease in PNN intensity followed by a nighttime increase was shown in regions associated with decision making, learning, memory processing, and sleep (prelimbic area (PLA) and infralimbic area (ILA) of prefrontal cortex (PFC), hippocampus, amygdala, thalamic reticular nucleus), in adult C57BL/6J mice.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in PFC function underly numerous psychiatric disorders including bipolar, post-traumatic stress disorder (PTSD), attention deficit disorder, and deficits in learning and memory (Popoli et al 2012; Sotres-Bayon, Cain, and LeDoux 2006; Miller and Cohen 2001; Xu et al 2019). There is growing evidence of links between circadian rhythms and PFC function (Otsuka et al 2020; Woodruff et al 2018; Hou et al 2022; Harkness et al 2021). Previous work from our group has demonstrated that extracellular lactate (a functional output of neural metabolism) shows circadian rhythms in the medial (m) PFC, and that environmental circadian disruption alters the morphology of medial mPFC neurons and affects PFC mediated behaviors (Wallace et al 2020; Karatsoreos et al 2011).…”
Section: Discussionmentioning
confidence: 99%